Raising Students’ Awareness on the Importance of Cohesion in Academic Writing: The Case of the Students of the Second Year English at Hamma Lakhdar University in El-Oued, Algeria - GHEDEIR BRAHIM, Mohammed; NESBA, Asma (University of eloued جامعة الوادي, 2017)
Using linguistic ties makes the students' written productions more cohesive and understandable. However, it is noticed that they do not use grammatical cohesive devices efficiently. Thus, the present study attempts to measure the students' awareness on the importance of cohesion in academic writing. Meanwhile, this research work aims at investigating the various kinds of grammatical cohesive devices used by the students and their effects on writing cohesive discourse. It is hypothesized that the accurate use of grammatical cohesive devices would enhance students' writing. Seeking to achieve the study's aims, two questionnaires have been administered to four teachers of written expression in addition to twenty five students who have been chosen randomly. The findings of the study revealed that students do not pay much attention to the significant decisive role of cohesion in written discourse. Hence it was suggested that much space should be dedicated to the issue of cohesion in written expression course. إن استخدام الروابط اللغوية يجعل المنتج الكتابي للطلبة أكثر تماسكا وفهما. ومع ذلك فانه يلاحظ أن هؤلاء الطلبة يفتقدون الكفاءة لاستخدام هذه الروابط اللغوية لبناء تماسك النص. وعليه، تعد هذه الدراسة محاولة جادة لقياس وعي الطلبة بأهمية التماسك في الكتابة الأكاديمية. تهدف هذه الدراسة إلى البحث في أدوات بناء التماسك النحوي المستعملة من لدن الطلبة وآثارها على كتابة خطاب مكتوب محكم التماسك. إن الفرضية التي بنيت عليها هذه الدراسة مفادها أن الاستخدام الصحيح لأدوات بناء التماسك النحوي تعزز التحكم في مهارة الكتابة عند الطلبة. وسعيا لتحقيق أهداف هذه الدراسة، تم تقديم استبيانين لأربعة أساتذة لمادة التعبير الكتابي بالإضافة إلى خمسة وعشرين طالبا تم انتقائهم عشوائيا. وقد كشفت نتائج الدراسة أن الطلبة لا يولون اهتماما كبيرا للدور الجوهري والهام لتماسك النص. كما نبهت الدراسة إلى ضرورة تخصيص حيز كبير من الوقت لموضوع تماسك النص في البرامج المخصصة لمادة التعبير الكتابي.
International Conference Organized by the Department of French Faculty of Letters and Languages University of Blida 2
Keywords: academic writing, awareness, cohesion; grammatical cohesion, lexical cohesion.; الكتابة الأكاديمية، الوعي، التماسك، التماسك النحوي، التماسك المعجمي